2015
DOI: 10.1177/1535370214563893
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-143 is associated with the survival of ALDH1+CD133+ osteosarcoma cells and the chemoresistance of osteosarcoma

Abstract: This study investigated the role of miR-143 in the chemoresistance of osteosarcoma tumor cells and the associated mechanisms. Real-time PCR was used to measure miR-143 levels. Western blot was used to detect protein expression. Cell proliferation was analyzed by MTT assay and Matrigel colony formation assay. Forced miR-143 expression was established by adenoviral vector infection. Cell death was detected by Hoechst33342 staining. Loss of miR-143 expression was observed in osteosarcomas, which correlated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 23 publications
(22 reference statements)
1
53
1
1
Order By: Relevance
“…1 The proliferation and invasion of tumor cells are considered as the foundation of cancer survival and development. Accumulating evidences demonstrated that the induction of epithelial-mesenchymal transition (EMT) and aberrant expression of microRNAs (miRNAs) are associated with tumorigenesis, tumor progression, metastasis and relapse in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…1 The proliferation and invasion of tumor cells are considered as the foundation of cancer survival and development. Accumulating evidences demonstrated that the induction of epithelial-mesenchymal transition (EMT) and aberrant expression of microRNAs (miRNAs) are associated with tumorigenesis, tumor progression, metastasis and relapse in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis, also termed programmed cell death, serves an important function in maintaining the normal physiological equilibrium of the human body and the elimination of old cells (24). Apoptosis is a process by which a gene actively determines the automatic life termination of a cell.…”
Section: Discussionmentioning
confidence: 99%
“…With high malignant degree and poorer prognosis, osteosarcoma seriously influences the prognostic survival of patients. Although the present classical surgery combined with neoadjuvant chemotherapy can significantly improve patient's life quality and raise the survival rate, the relapse, metastasis and multi-drug resistance to chemotherapy heavily threaten the long-term survival rate of patients [2][3][4] . Therefore, it is very important to enhance the sensitivity of osteosarcoma to chemotherapy and study its molecular mechanism during the process of clinical treatment.…”
Section: Introductionmentioning
confidence: 99%